The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1111/jce.16208
|View full text |Cite
|
Sign up to set email alerts
|

Catheter–tissue contact optimizes pulsed electric field ablation with a large area focal catheter

Shephal K. Doshi,
Mary Clare Flaherty,
Jacob Laughner
et al.

Abstract: IntroductionPulsed electric field (PEF) ablation relies on the intersection of a critical voltage gradient with tissue to cause cell death. Field‐based lesion formation with PEF technologies may still depend on catheter–tissue contact (CTC). The purpose of this study was to assess the impact of CTC on PEF lesion formation with an investigational large area focal (LAF) catheter in a preclinical model.MethodsPEF ablation via a 10‐spline LAF catheter was used to create discrete right ventricle (RV) lesions and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some researchers have also found that the PFA technology has better transmural damage ability than thermogenic ablation and can effectively block the reconnection of pulmonary veins compared with other ablation methods. At the same time, researchers have found that the PFA technique has better transmural damage ability than thermal ablation, and the lesion area has a high degree of consistency in regional width, homogeneous tissue fibrosis in the region, and is able to block the reconnection of the pulmonary veins more effectively than other ablation methods [ 35 , 43 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussion and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have also found that the PFA technology has better transmural damage ability than thermogenic ablation and can effectively block the reconnection of pulmonary veins compared with other ablation methods. At the same time, researchers have found that the PFA technique has better transmural damage ability than thermal ablation, and the lesion area has a high degree of consistency in regional width, homogeneous tissue fibrosis in the region, and is able to block the reconnection of the pulmonary veins more effectively than other ablation methods [ 35 , 43 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussion and Analysismentioning
confidence: 99%
“…The results showed that both left and right atrial ablation lesions were permeable to the wall, with a maximum thickness of 8–12 mm of ablated tissue, and sectioned histology revealed a highly uniform width of the lesion area and no arrhythmias or other complications during the procedure. A similar study was conducted by Doshi et al [ 53 ] where PFA ablation was performed on 10 pigs and the experimental pigs were divided into two subgroups: 8 experimental pigs were debrided 2 h after ablation and 2 experimental pigs were debrided 30 days after ablation. The permeability of each lesion was examined using staining.…”
Section: Pulsed-field Ablation: Biological Experimental Studymentioning
confidence: 99%